Photogrammabot: An Autonomous ROS-Based Mobile Photography Robot for Precise 3D Reconstruction and Mapping of Large Indoor Spaces for Mixed Reality - Mortezapoor, Soroosh; Schonauer, Christian; Ruggeberg, Julien; Kaufmann, Hannes (2022 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2022)
Precise 3D reconstruction of environments and real objects for Mixed-Reality applications can be burdensome. Photogrammetry can help to create accurate representations of actual objects in the virtual world using a high number of photos of a subject or an environment. Photogrammabot is an affordable mobile robot that facilitates photogrammetry and 3D reconstruction by autonomously and systematically capturing images. It explores an unknown indoor environment and uses map-based localization and navigation to maintain camera direction at different shooting points. Photogrammabot employs a Raspberry Pi 4B and Robot Operating System (ROS) to control the exploration and capturing processes. The photos are taken using a point-and-shoot camera mounted on a 2-DOF micro turret to enable photography from different angles and compensate for possible robot orientation errors to ensure parallel photos. Photogrammabot has been designed as a general solution to facilitate precise 3D reconstruction of unknown environments. In addition we developed tools to integrate it with and extend the Immersive Deck™ MR system [23], where it aids the setup of the system in new locations.